1986
DOI: 10.1085/jgp.88.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and adaptation of Limulus ventral photoreceptors by inositol 1,4,5 triphosphate result from a rise in intracellular calcium.

Abstract: Single pressure injections of 1-10 pl of inositol 1,4,5 triphosphate (IP3) or inositol 4,5 bisphosphate [I(4,5)P2] excite Limulus ventral photoreceptors by inducing rapid bursts of inward current. After excitation by IP3, responses to subsequent injections of IP3 or light flashes are often reversibly diminished (adapted). Single injections of IP3 and I(4,5)P2 are effective at concentrations in the injecting pipette of 20 microM to 1 mM. Single injections of inositol 1,4 bisphosphate are ineffective at concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(64 citation statements)
references
References 33 publications
5
58
1
Order By: Relevance
“…Subsequent injections of 100 mM EGTA, however, steadily attenuated and eventually irreversibly abolished the response to InsPs, as reported previously (Payne et al, 1986b). These experiments indicated that EGTA remaining at the injection site is saturated by the calcium released 750 ms later by a subsequent InsP3 injection and is therefore unable to reduce the consequent depolarization.…”
Section: Injection Of Egta or Bapta Reverses Desensitization Of Insp3supporting
confidence: 86%
See 3 more Smart Citations
“…Subsequent injections of 100 mM EGTA, however, steadily attenuated and eventually irreversibly abolished the response to InsPs, as reported previously (Payne et al, 1986b). These experiments indicated that EGTA remaining at the injection site is saturated by the calcium released 750 ms later by a subsequent InsP3 injection and is therefore unable to reduce the consequent depolarization.…”
Section: Injection Of Egta or Bapta Reverses Desensitization Of Insp3supporting
confidence: 86%
“…This buffering might mask the relief of feedback inhibition by injections of EGTA. High concentrations of EGTA have clearly been shown to antagonize the response to InsP3 (Rubin and Brown, 1985;Payne et al, 1986b). In the experiments described below, a second injection of InsP3 was delivered 750 ms after the injection of a solution containing 1 mM EGTA.…”
Section: Injection Of Egta or Bapta Reverses Desensitization Of Insp3mentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological and anatomical consequences of illumination have been well defined. In Limulus ventral photoreceptors, light-induced production of InsP 3 causes the release of calcium from intracellular stores (Brown and Rubin, 1984;Payne et al, 1986b), leading to the opening of nonspecific cation channels in the plasma membrane and a resulting depolarization of the photoreceptor's membrane potential. Calcium release subsequently reduces the photoreceptors' sensitivity, initiating light adaptation (Brown and Lisman, 1975).…”
Section: Abstract: Limulus Polyphemus; Photoreceptor; Pkc; Phototranmentioning
confidence: 99%